Semiotic Study On The Elements Of Architectural Spaces In The Compound Of Istana Alwatzikhoebillah Sambas (Case Study: Istana Kesulthanan Islam Sambas, Kalimantan Barat) - Alwin Fahreza; Sudaryono Sastrosasmito (Journal of Architectural Research and Design Studies, 2018)
Semiotic approach in architecture aims to promote understanding and discussion on architectural works among people. In this research, the architectural works refer to signs in the form of architectural elements found in the compound of Istana Alwatzikhoebillah of The Sultanate of Sambas. The Sultanate of Sambas is an Islamic kingdom acknowledged since the 16th century. The present building of Istana Alwatzikhoebillah is the result of a renovation carried out in 1931, thus has been standing for 89 years. The objective of this research is to figure out the relationship between the signs situated in the architectural spaces around the compound of Istana Alwatzikhoebillah by employing Pierce’s semiotic theory. This qualitative research uses rationalist paradigm with interview and observation as the data collection techniques. The collected data are analyzed using the diagram of Pierce’s triadic model of sign, which consists of object, interpretant, and representamen. Through the finding, this research suggests the meaning represented by each element of the architectural spaces, which are Kalling Jembatan, Gerbang Segilapan, Alon-Alon Istana, Tiang Kapal, and Gerbang Dalam Istan. Those five signs form a relational meaning which serves as a layered security architecture for Jalur Sulthan.Keywords: Semiotics, Sign, Architectural Elements, Istana Alwatzikhoebillah, Sambas.